Prevalence of Class II and III Obesity with Diabetes Type II and Associated Factors - Saleh Shah, Aamir Gul Memon, M. Imran Hussain, Maryam, Shamshad Gul, Mawra Urooj Memon, Kashaf Inam, Fatima Chaudhary (Pakistan Journal of Medical & Health Sciences, 2022)
Background: Obesity is related to Type II Diabetes (T2DM), affecting health-related quality of life. Body mass index (BMI) is a standardized screening tool used for Obesity. Gaining weight is highly associated with developing certain metabolic disorders, such as T2DM, which may worsen the quality of life. Among the general Pakistani population prevalence of overweight individuals is 25%, and obesity is 10.3%. Aim: To find out the prevalence of class II and III obesity with T2DM and associated factors Methods: This cross-sectional study was carried out at different clinics of Sindh. The study duration was six months, from February 2022 to July. Through a purposive sampling technique, 200 overweight males and females were selected. BMI was calculated by weight (kg) and Height (inches). Self-structured questionnaire for demographic and related associate factors. Results: The most subjects were fall into the age range above 46 years (67%) majority were male, 143(71.2%), most subjects were lies in class III obesity (65.5%) and 121(60.5%) were chronic smokers. The prevalence of T2DM among people aged ≥46 years was 58.2%. Outcomes on the gender bases showed that T2DM was higher at 73(51.1%) among males than females at 25(43.86%). The incidence of Diabetes was comparatively high among obese class III 81(61.8%) than class II individuals. Practical Implications: The Overweight individuals with type 2 diabetes face a chronic, developing disease that leads to complications that profoundly affect both quality of life and longevity. Diet recommendations to prevent T2DM should focus more on the quality of fat and carbohydrate in the diet than quantity alone, in addition to balancing total energy intake with expenditure to avoid obesity. Conclusion: It is concluded that the high prevalence of T2DM with obesity class III and chronic smokers among participants. Keywords: Associated factors, BMI, Diabetes, Obesity, Prevalence Smokers